2016
DOI: 10.17161/jomr.v2i1.5677
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Comparison of Montessori versus Non-Montessori Students’ Place-Value and Arithmetic Knowledge

Abstract: Abstract. Understanding of base 10 and place value are important foundational math concepts that are associated with higher use of decomposition strategies and higher accuracy on addition problems (Laski, Ermakova, & Vasilyeva, 2014;Fuson, 1990;Fuson & Briars, 1990; National Research Council, 2001). The current study examined base-10 knowledge, place value, and arithmetic accuracy and strategy use among children in early elementary school from Montessori and non-Montessori schools. Children (N = 150) were ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Our study focused on teacher knowledge for teaching in an education system as characterized by the Montessori curriculum, learning philosophies, classroom and assessment practices (Bagby & Sulak, 2010;Erwin et al, 2010;Lillard, 2011). Akin to Kayili and Ari (2011), Kuennen andBeam (2020), andLaski et al (2016), our study looked specifically at mathematics teaching particularly teacher knowledge needed, used and further honed by teachers to teach mathematics. Findings of this study are in Interview Excerpts on Independently understanding the mathematics concepts T01: In our philosophy the children work for themselves.…”
Section: Discussion Of Findings Mathematics Teacher Knowledge and Teaching Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focused on teacher knowledge for teaching in an education system as characterized by the Montessori curriculum, learning philosophies, classroom and assessment practices (Bagby & Sulak, 2010;Erwin et al, 2010;Lillard, 2011). Akin to Kayili and Ari (2011), Kuennen andBeam (2020), andLaski et al (2016), our study looked specifically at mathematics teaching particularly teacher knowledge needed, used and further honed by teachers to teach mathematics. Findings of this study are in Interview Excerpts on Independently understanding the mathematics concepts T01: In our philosophy the children work for themselves.…”
Section: Discussion Of Findings Mathematics Teacher Knowledge and Teaching Ecosystemmentioning
confidence: 99%
“…In the same way, other researches (see for example, Bagby & Sulak, 2010;Cossentino, 2005;Shiraz & Quisar, 2017) compared pedagogical practices of the Montessori systems to public schooling systems and noted relations to learning theories in Montessori education that focus on constructivism (Bagby & Sulak, 2010), playful and mindful learning (Lillard, 2007(Lillard, , 2013, student motivation (Rathunde & Csikszentmihalyi, 2005) and development of executive and transferrable skills among learners (Franczak, 2016). In line with the above learning theories, Cossentino (2009), and Beatty's (2011) research studies focus on teacher education, whereas Faryadi (2017), and Laski et al (2016) focus specifically on Montessori mathematics education with emphasis on pedagogies that would aid learners' understanding and construction of their own learning.…”
Section: Montessori Education Philosophymentioning
confidence: 99%
“…They found that students from classrooms in which non-Montessori supplementary materials had been removed made greater gains on assessed measures over 4 months than students from the classrooms with mixed materials. This study is critical in light of other studies that have reported little or no difference in gains for students from Montessori versus non-Montessori classrooms (Laski, Vasilyeva, & Schiffman, 2016).…”
Section: Heightened Learning Experiencementioning
confidence: 94%
“…Findings are also inconsistent. For instance, while some studies have found that children in Montessori classrooms have better reading (Lillard, 2012;Lillard & Else-Quest, 2006), math (Chisnall & Maher, 2007;Denervaud, Knebel, Hagmann, & Gentaz, 2019;Laski, Vasilyeva, & Schiffman, 2016;Lillard & Else-Quest, 2006), executive functions (Denervaud et al, 2019;Lillard, 2012;Lillard & Else-Quest, 2006), and social skills (Lillard, 2012;Lillard & Else-Quest, 2006;Lillard et al, 2017) than children in conventional classrooms, other studies have found no advantage on similar measures of math (Chisnall & Maher, 2007;Lillard, 2012;Mix, Smith, Stockton, Cheng, & Barterian, 2017), executive functions (Denervaud et al, 2019;Lillard & Else-Quest, 2006;Lillard et al, 2017), and social skills (Lillard, 2012;Lillard et al, 2017). Figure S1 summarizes the number of previously reported effects in favor or against Montessori preschool education as a function of the domain.…”
Section: Previous Research On Montessori Preschool Educationmentioning
confidence: 99%